Lymphocyte Phospho-Ser-9-GSK-3β/Total GSK-3β Protein Levels Ratio Is Not Affected by Chronic Lithium or Valproate Treatment in Euthymic Patients With Bipolar Disorder. Issue 2 (April 2017) - Azab, Abed N.; Vainer, Ella; Agam, Galila; Bersudsky, Yuly
Abstract: Background: Glycogen synthase kinase-3 (GSK-3) inhibition by lithium has been well established in vitro, but proof that this biochemical effect mediates lithium's beneficial action in patients with bipolar disorder is lacking. We studied whether lymphocyte GSK-3β activity measured indirectly in lithium- or valproate (VPA)-treated euthymic patients with bipolar disorder is different from controls. Methods: Lymphocyte total and Ser-9-phospho-GSK-3β (inactive) levels were measured by Western blotting. Forty-seven patients with bipolar disorder and 32 age- and sex-matched control subjects were studied. Results: No significant differences were found between lithium- and VPA-treated patients and controls in phospho-GSK-3β, total GSK-3β, or their ratio. Conclusions: The data do not support the concept that in vivo, during chronic treatment of bipolar illness, GSK-3β is inhibited either by lithium or by VPA.